(untitled) (Povijesni prilozi (Historical Contributions), 2025)
By late summer 1620, the fires of the Thirty Years’ War were spreading towards the Kingdom of Croatia and Slavonia and the provinces of Inner-Austria. Moreover, the very survival of the Habsburg Monarchy was being put to the test. In the short period between 1619 and 1620, Emperor and King Ferdinand II, as the newly elected and installed Habsburg ruler, lost both the Bohemian and Hungarian crowns due to the rebellious Bohemian and Hungarian estates. To make matters worse, these two estates had joined the alliance known as the Bohemian Confederation. Ferdinand found himself in a desperate position, with his rule largely dependent on foreign support. Yet, there were lands within the Habsburg Monarchy still loyal to the House of Austria – specifically, the Catholic Hungarian estates, Inner-Austrian provinces and the Kingdom of Croatia and Slavonia. Even though Croatia and Slavonia were part of the Realm of Saint Stephen alongside Hungary, in August 1620 they rejected Gabriel Bethlen as an elected king of Hungary unlike many members of the Hungarian aristocracy and opposed the decisions of the Hungarian Diet. Their long-standing military and political cooperation with the Inner-Austrian provinces, which had lasted for over a century, contributed to this alignment. Ferdinand II encouraged a meeting between Croatian-Slavonian and Inner-Austrian estates of the two sides in hope of arranging a viable defensive system. First, they assembled in Zagreb, where the members of the Croatian-Slavonian Diet proposed several solutions, including the establishment of a military alliance or a formal confederation with the Inner-Austrian provinces. These negotiations continued in Graz, where further deliberations were held and concrete military decisions regarding joint defence were adopted.